Conceptual Fire Risk Management Framework of Building Information Modeling and Fire Dynamic Simulator - Chung Sum Leong; See Hung Lau; How Hui Liew (Engineering Proceedings)
Fires in buildings result in the undesirable loss of life and property. Despite fire safety designs, the frequent occurrence of fires indicates a need for improvements in fire safety management. Conventional fire safety management is based on regulations managed separately by different parties at various stages of a building’s lifecycle. This study aims to present a conceptual framework for building information modeling (BIM)-based fire safety and risk management using the fire dynamics simulator (FDS) for a three-story building. A BIM model was developed for the building with fire safety compliance checks, and a simulation was conducted using FDS to integrate the results into the BIM model and test the model’s feasibility. The framework process consists of modeling, analysis, data integration, and user education. The BIM model was developed using Revit during the modeling stage and evaluated for fire safety compliance using Dynamo scripts. Concurrently, FDS simulations were performed for fire risk assessment in various scenarios, and evacuation route planning was established, considering the available evacuation time obtained from FDS results. Fire safety information, such as available evacuation time and optimal evacuation paths, was then integrated back into the BIM model for data integration using Dynamo scripts. In the model, fire safety compliance and simulation results were successfully integrated into the BIM model, serving as a platform for effective fire safety and risk management and providing fire safety information for building residents.